A preliminary study on the preservation of climbing perch Anabas testudineus Bloch, 1792 (Pisces: Anabantidae) oocytes using dry method at different temperature - Gheitsa, Tjut N.G.; Maulida, Siti; Muchlisin, Zainal Abidin (Aceh Journal of Animal Science, 2023)
Climbing perchAnabas testudineusis a freshwater fish that has economic value and has been cultivated in Indonesia. However, the fish farmers face problems with high-quality larvae supply because the breeding technology for this species is not well developed. Sperm and oocyte storage technology is important information in fish breeding. Therefore, this research aims to determine the best storage temperature using the dry storage method. Six levels of storage temperatures were tested in this study, namely: 29C (room temperature as a control), 8C, 4C, 0C, -4C, and -8C. The oocytes are stored at the treatment temperature for 120 minutes, where every 30 minutes the quality of the oocytes is analyzed based on fertilization and hatchability parameters. The results showed thatstorage temperature had a significant effect on fertility (P0.05) but had no significant effect on hatchability or the normality of larvae (P0.05). The highest percentage of fertility was obtained in treatment B (8C) at 30 minutes, with a value of 50.33%; this value was significantly different with other treatments. The highest hatchability percentage value was also obtained in treatment B (8C) at 30 minutes, with a value of 12%. This value was significantly different in treatments E (-4C) and F (-8C), but not significantly different with treatments A (29C), C (4C), and D (0C) (P 0.05). The directobservations on the normality of the hatched larvae showed that all larvae had a normal morphology. In general, fertility and hatchability rate decrease with decreasing temperatures. Therefore, it is concluded that climbing perch fish eggs stored using the dry method can only be stored for less than 30 minutes, where the recommended temperature was 8C.